Social representations that orient the fertility of women of 20 to 29 years old in three socioeconomic contexts - Fuentes Rodríguez, Eugenio (2009)
The process of demographic transition in Costa Rica produced a reduction of the differential fertiliy. The disparities can be explained by sociocultural, space and structural heterogeneity of the Costa Rican society. In terms of etaries groups, the women between 20 and 29 years old have contributed mainly to this reduction. The investigation had as objective investigate the manifestation of the diffusion process of innovations in the Costa Rican fertility, through the social representations of the contraceptive methods and the maternity, in women between 20 and 29 years old of three communities of the country. From the statistical analysis for 446 districts with data of reduction of the fecundity and the mother's socioeconomical level (level of instruction, conjugal union and occupation) between 1995-1997 and 2002-2004; three districts were selected to make in-depth interviews (Sánchez of Curridabat, Tarbaca of Aserrí and Tayutic of Turrialba). It was found that the socializing agents of the sexual education (formal education, mass media, religion, health service and family), are not fulfilling a role of quality information on the biological reproduction, and causes a conductual diffusion more than material, framed within the patriarcal tradition that relegates the woman to the social reproduction. Between the interviewed people from the three districts remain inequalities of information access and regarding life projects that go beyond the private scope, helping to support social inequities that are reflected in the current differential fertility.